Gestión Administrativa-Financiera y su relación con el cumplimiento de metas del departamento de tesorería del g.a.d. municipal de San Jacinto de Buena Fe, año 2013 - Cedeño Briones, Ana Estefanía (2015)
This thesis entitled "Administrative and financial management and its relationship to the fulfillment of goals treasury department of GAD City of San Jacinto de Buena Fe, period 2013", has the following objectives: to analyze the existence of plans, procedures, objectives and coherent policies employed by the GAD City of San Jacinto de Buena Fe, check with profitability indicators if the institution distributes its resources effectively, investigate internal control that uses the Municipal GAD San Jacinto de Buena Fe to comply with the goals and objectives. This research was based scientific information which allowed to take concepts, theories and thoughts of others that deal with the topic investigated. For the implementation of this project was used to used methods, techniques and types of research that allowed them to achieve their objectives. The results obtained at the end of the investigation to the Municipal GAD Good Faith reflected that do exist plans, procedures, objectives and coherent policies employed in the opinion of the Head of Treasury, because the activities are developed on this basis, it was found the distribution of resources by profitability indicators, the same as resulted in a net profit margin of 32.29%, which means that they can continue to invest in other productive sectors and thus increase the level of profitability, in terms of costs is 13.45%, which means an excess in public procurement, the City of San Jacinto GAD de Buena Fe to comply with the goals and objectives if you use proper internal control because according to 60% of the respondents, institution communicates time for citizens dates that must comply with the payment of taxes, plus 51.92% said that if they are informed while the budget for revenues and expenses.